Jawabanmu

2014-01-16T22:36:44+07:00
Pake teorema sisa
b+ax-4x^2+8x^3 dibagi x+1, sisa -19
maka b+a(-1)-4(-1)^2+8(-1)^3=-19\\
b-a-4-8=-19\\
b-a=-19+4+8\\
b-a=-7\\
a-b=7


b+ax-4x^2+8x^3 dibagi 2x-1, sisa 2
maka  b+a( \frac{1}{2}) -4( \frac{1}{2})^2+8( \frac{1}{2})^3=2\\\\
b+( \frac{a}{2})-4( \frac{1}{4})+8( \frac{1}{8})=2\\\\
b+\frac{a}{2}-1+1=2\\\\
b+\frac{a}{2} =2\\\\
\frac{a}{2}+b =2\\\\
a+2b =4\\\\


kedua persamaan tadi dieliminasi dan substitusi,
didapat 
a = 6
b = -1


2014-01-17T00:37:19+07:00